Nilai Teori Konstitusi Nusantara dalam Tradisi Pengobatan Lisan dan Peran Apoteker Modern - Sudrajat, Hendra; Rahmawati, Nur (Jurnal Medika Farmaka, 2025)
This study examines the integration of the values of the Indonesian Constitution, particularly the teachings of Sunan Drajat, into oral medicine practices and their relevance to the role of modern pharmacists. Values such as empathy, social justice, and community-based services embodied in Sunan Drajat's Pepali Pitu and Catur Pitulung demonstrate substantial alignment with the ethics of the pharmaceutical profession. This study employed a qualitative-descriptive approach through literature review, normative analysis, and historical methods. The results demonstrate that these values can be systematically integrated into the curriculum, training, and practice of pharmacists. Visualizations through diagrams and graphs demonstrate increased public trust in pharmacists based on local values. This integration serves as a foundation for strengthening a healthcare service model that is not only clinical but also rooted in the culture and spirituality of the community.